1991
DOI: 10.1128/iai.59.12.4647-4654.1991
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th2 cytokine secretion patterns in murine candidiasis: association of Th1 responses with acquired resistance

Abstract: Two chemically mutagenized agerminative variants of Candida albicans were used to immunize mice against challenge with highly virulent cells of the parent strain. Although both mutants (Vir-3 and Vir-13) resulted in nonlethal infection and could be recovered from mouse organs for many days after the intravenous inoculation of 10' to 106 cells, significant protection to systemic challenge with virulent C. albicans was induced by only one (Vir-3) of the two variants. Anticandidal resistance in Vir-3-infected mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
116
0
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(124 citation statements)
references
References 47 publications
(49 reference statements)
6
116
0
2
Order By: Relevance
“…These findings suggest that the immune defects seen in CMC are perhaps not as selective or subtle as previously supposed. Data obtained on animal (murine) models have shown that resistance to systemic and mucosal candidiasis is closely associated with a Th1 type of response characterized by increased production of IFN-, IL-2, and enhanced DTH, while susceptibility is accompanied by a Th2 type response with increased IL-4 and IL-6 production [8]. Administration of anti-IL-4 antibody in this model resulted in increased survival [9].…”
Section: Introductionmentioning
confidence: 70%
“…These findings suggest that the immune defects seen in CMC are perhaps not as selective or subtle as previously supposed. Data obtained on animal (murine) models have shown that resistance to systemic and mucosal candidiasis is closely associated with a Th1 type of response characterized by increased production of IFN-, IL-2, and enhanced DTH, while susceptibility is accompanied by a Th2 type response with increased IL-4 and IL-6 production [8]. Administration of anti-IL-4 antibody in this model resulted in increased survival [9].…”
Section: Introductionmentioning
confidence: 70%
“…Non-specific immune responses, expressed by activation of polymorphonuclear neutrophils [28][29][30] and macrophages [31,32], have been shown to be involved in the resistance to the early phase infection with C. albicans. A major influence in host resistance against systemic C. albicans infection is a type 1 T cell-associated cellular response (type 1 T cell response) [33][34][35][36][37][38]. Type 1 T lymphocytes produce type 1 cytokines (IL-2 and IFN-g) following appropriate stimulation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 T lymphocytes produce type 1 cytokines (IL-2 and IFN-g) following appropriate stimulation [34]. These type 1 cytokines are able to activate and enhance killing activities of effector cells (cytotoxic T lymphocytes, natural killer cells, macrophages and neutrophils) targeted to cells infected with C. albicans [34][35][36][37][38][39]. However, type 1 T cell responses are generally suppressed by type 2 cytokines (IL-4 and IL-10) [40][41][42] released from T helper type 2 cells (Th2 cells) or CD8 þ type 2 T cells [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The association between vaginal candidiasis with a type 2 immune response has been well documented in experimental models of candidiasis. While in the CBA/j mice, a type 1 immune response is generated with subsequent control of infection, BALB/c mice produce predominantly IL-4 and have recurrent infections [10]. This may imply that type 1 immune reactivity is associated with resistance to candidal disease, while type 2 immune responses are associated with pathology of RVC.…”
Section: Introductionmentioning
confidence: 99%